Finansowe determinanty zaspokajania potrzeb mieszkaniowych - Maciejasz-Świątkiewicz, Marta (Financial Determinants of Housing Needs Fullfilment, 2005)
This article presents theoretical models of housing financing and their practical usage. The main thesis is that housing market is not perfect and cannot react automatically. Thus it needs some support from public funds and specially adapted financial instruments to fullfil housing needs of society. As the biggest problem is connected with too small demand, instruments must be directed to the housing consumers (owners and renters).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 75-88